1995
DOI: 10.1002/ppul.1950200407
|View full text |Cite
|
Sign up to set email alerts
|

Home testing for pediatric obstructive sleep apnea syndrome secondary to adenotonsillar hypertrophy

Abstract: The objective of this study was to determine the accuracy and practicality of home testing for pediatric obstructive sleep apnea syndrome (OSAS) secondary to adenotonsillar hypertrophy. Twenty-one children aged 2-12 years and referred for possible OSAS were studied twice, once at home and once in the sleep laboratory. The home test consisted of two parts: 1) a cardiorespiratory recording of saturation (SaO2), pulse rate, pulse waveform, electrocardiogram, and respiratory inductive plethysmography; and 2) an 8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
0
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 38 publications
3
107
0
6
Order By: Relevance
“…This scoring system (Table 1) was then applied to the overnight oximetry tests performed as part of in-laboratory PSG or a home cardiorespiratory sleep study (CRSS) 18 for evaluation of suspected OSA between 1992 and 1998. Detailed information on the perioperative course of children in this cohort has been published previously.…”
Section: Phase 2: Retrospective Validation Of the Scorementioning
confidence: 99%
“…This scoring system (Table 1) was then applied to the overnight oximetry tests performed as part of in-laboratory PSG or a home cardiorespiratory sleep study (CRSS) 18 for evaluation of suspected OSA between 1992 and 1998. Detailed information on the perioperative course of children in this cohort has been published previously.…”
Section: Phase 2: Retrospective Validation Of the Scorementioning
confidence: 99%
“…Details of our sleep study recording systems have been published elsewhere. [9][10][11][12] Although the studies were analyzed for several variables, 5 only the OAH index and the preoperative saturation nadir (preSaO 2 nadir) are reported. The preSaO 2 nadir was defined as the minimum hemoglobin oxygen saturation regardless of duration and was validated by visual inspection of a computerized data record.…”
Section: Chart Review and Study Parameters Diagnostic Criteria For Osasmentioning
confidence: 99%
“…This is based on the assumption that if detection of rapid-eye-movement sleep (when OSA is usually present or most severe) is not possible, OSA cannot be reliably ruled out. Three validation studies on abbreviated HPSG showed conflicting results [53][54][55]. However, as previously discussed by MORIELLI et al [56] and JACOB et al [54] there is invariably rapid-eye-movement sleep present in an all night recordings, even though it may not be possible to determine which specific epochs are included.…”
Section: Sleep-related Disorders Ms Urschitz Et Almentioning
confidence: 65%
“…Three validation studies on abbreviated HPSG showed conflicting results [53][54][55]. However, as previously discussed by MORIELLI et al [56] and JACOB et al [54] there is invariably rapid-eye-movement sleep present in an all night recordings, even though it may not be possible to determine which specific epochs are included. Meanwhile, abbreviated HPSG has been used by a series of other community-based studies [6,10,12,14], possibly because full HPSG suffers from significant artefacts in the electroencephalographic and myographic channels [57].…”
Section: Sleep-related Disorders Ms Urschitz Et Almentioning
confidence: 65%
See 1 more Smart Citation